Peningkatan Kecerdasan Logika Matematika Anak Usia 5-6 Tahun Melalui Penggunaan Media Pohon Pintar di TK Cahaya Harapan Desa Muara Gusik - Aslindah, Andi; Ardiana, Reni; Paramita, Nurul (PT Literasi Nusantara Publisher, 2024)
This study aims to determine the improvement of mathematical logic intelligence for children aged 5-6 years through the use of smart tree media in Cahaya Harapan Kindergarten, Muara Gusik Village. This research was classroom action research (PTK) with four stages, namely planning, implementation, observation, and reflection. This research was planned in two cycles consisting of cycle I and cycle II, each cycle was carried out for 3 meetings. The results of the cycle were refined in the next cycle until you get maximum learning results. The research site was carried out in the age group of 5-6 years in Cahaya Harapan Kindergarten, Muara Gusik Village with a total of 13 children consisting of 7 boys and 6 girls. Based on the results of class action research that had been carried out, in cycle I the average score of children reached 59 with criterion B (Good) and a percentage of 42%, in cycle II the average score of children reached 75 with criterion A (Very good). This research was said to be successful because cycle I and cycle II experienced an increase in achieving good criteria and very good. The results of the class action research carried out showed that the use of smart tree media, could increase the mathematical logic intelligence of children aged 5-6 years in Cahaya Harapan Kindergarten, Muara Gusik Village.